Multiscale Modeling and Experimental Characterization for Enhancement in Electrical, Mechanical, and Thermal Performances of Lithium-Ion Battery - Snigdha Sharma; Snigdha Sharma; Amrish K. Panwar; M. M. Tripathi (Frontiers in Energy Research, 2022)
Lithium-ion batteries are the thriving energy storage device in multiple fields, including automobiles, smart energy grids, and telecommunication. Due to its high complexity in the electrochemical–electrical–thermal system, there are certain non-linear spatiotemporal scales for measuring the performance of lithium-ion batteries. The fusion of experimental and modeling approaches was used in this study to enhance the performance of lithium-ion batteries. This article helps to evaluate the properties of the LiMn2O4 cathode material for Li-ion batteries and also characterize the crystalline nature, morphological structure, and ionic and electronic conductivity of the electrode material using an experimental approach. In addition, a new computational model was designed and formulated to support various other models for computational investigation. This simulation was designed to analyze the one-dimensional structure of coin cell batteries and to evaluate electrochemical and thermal performances. All computational performances have been validated with the help of experimental techniques and also provide multiple benchmarks for future integration of experimental and computational approaches.